Atmospheric pollutants NO2 and O3 enhance allergenic potential of Dactylis glomerata pollen. - Costa, Ana R. (2020)
Background : Airborne pollen during its transport become in contact with a variety of atmospheric chemicals, including the common air pollutants O 3 and NO 2 . Nevertheless, the effect of these pollutants, alone or in combination, is not fully elucidated. With a strong oxidiz-ing potential, ozone may affect pollen redox balance and contribute to change the ratio of ROS scavenging enzymes and in the presence of NO 2 , may also contribute to the nitration of proteins, including allergens, affecting pollen allergenicity. Traffic- related pollution may as such contribute to an increased prevalence of pollen driven aller-gic diseases in urban areas. The goal of this research was to study the effects of O 3 , NO 2 and the mixture of both pollutants on IgE- reactivity patterns to Dactylis glomerata pollen, as well as on the levels of Dac g 5 and profilin by immunoblot. Method : D. glomerata pollen was treated in an environmental cham-ber during 6 hours. Protein extracts from unexposed (Control) or exposed to air pollutants (O 3 , NO 2 or O 3 +NO 2 ) pollen samples were prepared in phosphate buffered saline (PBS) and frozen until analy-sis. SDS- page separated proteins were blotted and used to obtain IgE- reactivity patterns with pooled sera (from four D. glomerata EAST- positive sera) and with antibodies against grasses group 5 al-lergens and profilin. Results : IgE- reactivity have shown bands with MW of 15, 29, 33, 37, 46, 52, 57, 60, 69 and 142 kDa (intensity >4%). Bands with 15, 57 and 60 kDa were intensified by NO 2 exposure compared to control. Pollen exposure to O 3 induced an amplification of IgE- reactivity in 40% of the detected bands (29, 33, 60, 66, 69, 74 and 80 kDa). Pollen exposed to O 3 +NO 2 showed augmented IgE- reactivity in bands with 14, 15, 18, 57, 66 and 80 kDa. Some of the bands identified to be affected by the pollen exposure to air pollutants of MW 29, 33 and 60 kDa, have correspondence to known allergens, respectively, Dac g 5, Dac g 1, Dac g 4. Additionally, immunoblot performed with IgG anti- Dac g 5 and anti- profilin confirmed overexpressed bands with, respectively, ~30 kDa and ~13 kDa, in O 3 treated pollen. Conclusion : D. glomerata pollen exposure to O 3 and NO 2 showed enhanced IgE recognition of several proteins, some of which are de-scribed allergens. These results suggest that common air pollutants contribute to an increased pollen allergenicity and directly correlat-ing with the higher incidence of respiratory allergic diseases in urban areas.